Penerapan Model Discovery Learning Berbantuan Simulasi PhET terhadap Hasil Belajar Siswa MTs NW Kilang - Sunni, M. Abdurahman; Nurlaeli, Nurlaeli (Lembaga Yasin AlSys, 2022)
This study is a quasi-experimental study with the aim of knowing the effect of applying the discovery learning model assisted by PhET simulation in science (physics) subjects on class IX students of MTs NW Kilang in the 2021/2022 academic year, totaling 60 students divided into 3 classes. This research was designed with Posttest Only Control Group Design. The sampling technique used cluster random sampling technique so that there were 25 students in class IXA as experimental class 1 (PhET assisted discovery learning) and 24 students in class IXB as experimental class 2 (discovery learning without PhET assistance). From the results of the study, it was found that the average value of learning in the experimental class 1 was higher than the learning in the experimental class 2, which was 73.55 for PhET-assisted discovery learning and 68.29 for discovery learning without the aid of PhET. Learning outcomes data were analyzed by spss statistics 26 t-test (Independent Samples T Test) and obtained a significance value of 0.037 <0.05, which means that there is a significant difference in learning outcomes in science (physics) using the PhET-assisted discovery learning model and discovery learning without the aid of PhET for class IX students at MTs NW Kilang for the 2021/2022 academic year.